What Sparks Student Investment? The Effects of Financial Literacy, Gender, and Income - Desiana, Rina; Fitria, Ana; Nada, Qathrin (Journal of Principles Management and Business, 2024)
This research aims to measure the influence of financial literacy, gender and income variables on investment interest. One of the quantitative methods used in this study is proportionate random sampling. 392 of the population participated in this study after filling in a Google Form questionnaire and were active students at UIN Ar-Raniry Banda Aceh. Multiple linear regression analysis was done. With the use of SPSS, gender was found to have a marginal effect on student’s investment interest in UIN Ar-Raniry Banda Aceh, while financial knowledge and income variables were found to have a very positive effect. The research and trial results show that F count > F table. For instance, if F count value 47.251 > F table 2.672 the level of significance for the p-value is smaller (<) than 0.05 (p=0). So that financial literacy, income, and gender simultaneously have an effect on the investment interest of student’s UIN Ar-Raniry Banda Aceh.